Genetic Markers in Biological Fluids for Aging-Related Major Neurocognitive Disorder - Castro-Chavira, S.A.; Fernandez, T.; Nicolini, H.; Diaz-Cintra, S.; Prado-Alcala, R.A. (Current Alzheimer Research, 2015)
Aging-related major neurocognitive disorder (NCD), formerly named dementia, comprises of the different acquired diseases whose primary deficit is impairment in cognitive functions such as complex attention, executive function, learning and memory, language, perceptual/motor skills, and social cognition, and that are related to specific brain regions and/or networks. According to its etiology, the most common subtypes of major NCDs are due to Alzheimer’ s disease (AD), vascular disease (VaD), Lewy body disease (LBD), and frontotemporal lobar degeneration (FTLD). These pathologies are frequently present in mixed forms, i.e., AD plus VaD or AD plus LBD, thus diagnosed as due to multiple etiologies. In this paper, the definitions, criteria, pathologies, subtypes and genetic markers for the most common age-related major NCD subtypes are summarized. The current diagnostic criteria consider cognitive decline leading to major NCD or dementia as a progressive degenerative process with an underlying neuropathology that begins before the manifestation of symptoms. Biomarkers associated with this asymptomatic phase are being developed as accurate risk factor and biomarker assessments are fundamental to provide timely treatment since no treatments to prevent or cure NCD yet exist. Biological fluid assessment represents a safer, cheaper and less invasive method compared to contrast imaging studies to predict NCD appearance. Genetic factors particularly have a key role not only in predicting development of the disease but also the age of onset as well as the presentation of comorbidities that may contribute to the disease pathology and trigger synergistic mechanisms which may, in turn, accelerate the neurodegenerative process and its resultant behavioral and functional disorders.
Keywords: neurocognitive disorder